2016
DOI: 10.2147/clep.s115565
|View full text |Cite
|
Sign up to set email alerts
|

Validation of diagnostic codes for Charcot-Marie-Tooth disease in the Danish National Patient Registry

Abstract: PurposeTo validate the diagnostic codes for Charcot–Marie–Tooth disease (CMT) in the Danish National Patient Registry (DNPR) using positive predictive value (PPV) as a measure of validity.Patients and methodsWe used the DNPR to identify all patients diagnosed with at least one primary CMT diagnosis at a specialized department in the Central Denmark Region during the period 1977–2012. From this population, we randomly selected 123 patients for the validation study. Medical files were reviewed and used as refere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 13 publications
1
9
0
1
Order By: Relevance
“… 8 We have previously reported a high validity of the CMT diagnoses, supporting the use of the DNPR in epidemiological research on CMT. 9 However, the CMT population in our study is not complete, as the DNPR only covers patients with hospital contact since 1977. Patients with milder signs and symptoms, or patients to whom CMT is already a well-known part of their family history, might never be referred to a hospital department.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“… 8 We have previously reported a high validity of the CMT diagnoses, supporting the use of the DNPR in epidemiological research on CMT. 9 However, the CMT population in our study is not complete, as the DNPR only covers patients with hospital contact since 1977. Patients with milder signs and symptoms, or patients to whom CMT is already a well-known part of their family history, might never be referred to a hospital department.…”
Section: Discussionmentioning
confidence: 99%
“… 8 In a previous study, the positive predictive value (PPV) of the CMT diagnoses in the DNPR was reported as 88.5%. 9 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Achados de pé cavo e dedos em martelo são frequentes, observados em mais de dois terços dos casos. Foram propostos sete critérios para o diagnóstico clínico (De Jonghe & Timmerman, 1997;Haites, Nelis, Van Broeckhoven, 1998), sendo que para a validação diagnóstica em pacientes dinamarqueses (Vaeth et al, 2016), foram considerados pelo menos um dos três primeiros e pelo menos quatro dos sete:…”
Section: Indroduçãounclassified